2021
DOI: 10.3233/jad-200735
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Optical Coherence Tomography Metrics Are Unchanged in Verubecestat Alzheimer’s Disease Clinical Trial but Correlate with Baseline Regional Brain Atrophy

Abstract: Background: We performed exploratory analyses of retinal thickness data from a clinical trial of the AβPP cleaving enzyme (BACE) inhibitor verubecestat in patients with Alzheimer’s disease (AD). Objective: To evaluate: 1) possible retinal thickness changes following BACE inhibition; and 2) possible association between retinal thickness and brain atrophy. Methods: Retinal thickness was measured using spectral-domain optical coherence tomography in a 78-week randomized placebo-controlled trial of verubecestat in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Instead, we focused on the association between retinal measures and hippocampal subfields. We found that thicker RNFL in the special sector showed significantly increased subiculum, presubiculum, GC-ML-DG and molecular_layer_HP volumes, which is consistent with previous studies [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Instead, we focused on the association between retinal measures and hippocampal subfields. We found that thicker RNFL in the special sector showed significantly increased subiculum, presubiculum, GC-ML-DG and molecular_layer_HP volumes, which is consistent with previous studies [ 35 , 36 , 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…One study found an inverse correlation between macular thickness and cerebral cortical atrophy, especially parietal cortical atrophy in AD patients [ 30 ]. Others revealed a significant positive correlation between RNFL thickness and hippocampal volume, with this association being more pronounced in the m-RNFL in people without dementia [ 35 , 36 , 37 ]. However, these studies were focused on the relationship between retinal structure and a relatively large area of the brain (i.e., temporal lobe, whole hippocampus) [ 35 , 36 , 37 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNFL thickness may also reflect cingulate cortex atrophy in individuals without dementia ( Shi et al, 2019a ). Other studies have reported a correlation between retinal thickness and brain structure in patients with AD, but these findings are inconsistent ( Yoon et al, 2019 ; Zhao et al, 2020 ; Sergott et al, 2021 ).…”
Section: Introductionmentioning
confidence: 89%